Investigation of Energy Transfer in a Blend of electroluminescent Conducting Polymers - Dinh, Nguyen Nang; Nam, Nguyen Phuong Hoai; Chung, Do Ngoc (Communications in Physics, 2011)
With the aim of improving the photonic efficiency of an organic light emitting diode a blend of electroluminescent polymers, poly[9-vinylcarbarzole] (PVK) and poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene] (MEH-PPV) was prepared. The energy transfer in the blend was investigated through the comparison of absorption, photoluminescence (PL) and current-voltage (I-V) characteristics of the blend and standard polymers. The obtained results showed that energy transfer from PVK to MEH-PPV enable to form localized excited-state complexes (e.g. exciplexes) in MEH-PPV. The PL intensity of the blended polymers was enhanced as the relative content of MEH-PPV was increased, and particularly, the highest improved PL was observed for an weight fraction of 15 wt{%} of MEH-PPV in PVK. Organic light emitting diodes made from these blends would exhibit a large photonic efficiency.